Common atrium and the associated malformations: Evaluation by low-dose dual-source computed tomography - Zhang, Yi (Medicine (Baltimore), 2018)
Common atrium (CA) is a rare complex congenital heart disease. The studies of CA are mostly case reports, while few have been done regarding its morphological characteristics. We aimed to determine CA characteristics and diagnostic accuracy in assessing associated malformations in these patients with low-dose dual-source computed tomography (DSCT). Twenty-one pediatric and adolescent CA patients underwent low-dose DSCT. Different ventricular types and associated malformations were assessed. The diagnostic accuracy of DSCT and transthoracic echocardiography (TTE) in evaluating associated malformations were assessed. The effective doses of DSCT were calculated. Patients (n = 21) were divided into CA with biventricular physiology (n = 7) and CA with single ventricle (SV) (n = 14). There were 3 types of SV morphology: single left ventricle (n = 5), single right ventricle (n = 6), and undifferentiated ventricle (n = 3). In all, 22 associated malformations were seen in CA and 56 in CA with SV. DSCT was superior to TTE for detecting intracardiac anomalies (sensitivity: DSCT, 92.31% vs TTE, 76.92%), great vessels anomalies (sensitivity: DSCT, 100.00% vs TTE, 77.50%), and of collateral vessels (sensitivity: DSCT, 100% vs TTE, 20.00%). The estimated mean effective dose was 0.95 ± 0.44 mSv (<1 mSv). This study indicated that low-dose DSCT is an ideal alternative for pediatric and adolescent patients with CA, providing morphological details of CA and associated malformations with high accuracy.